2020
DOI: 10.3389/fpls.2020.568890
|View full text |Cite
|
Sign up to set email alerts
|

Natural Plant Products: A Less Focused Aspect for the COVID-19 Viral Outbreak

Abstract: The sudden emergence of COVID-19 caused by a novel coronavirus (nCoV) led the entire world to search for relevant solutions to fight the pandemic. Although continuous trials are being conducted to develop precise vaccines and therapeutic antibodies, a potential remedy is yet to be developed. Plants have largely contributed to the treatment of several human diseases and different phytoconstituents have been previously described to impede the replication of numerous viruses. Despite the previous positive reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 85 publications
(116 reference statements)
0
28
0
2
Order By: Relevance
“…The SARS-CoV occurred in 2003, since then many natural products have shown potential in experimental studies to be developed as a candidate drug until recent years, but still there is very less focus on drug development from natural products due to numerous reasons ranging from lack of pharmacokinetic and drug formulation studies [ 204 , 205 , 206 ]. Recently, it has been suggested that a meticulous, focused and integrated approach may have the potential to develop the drugs from traditional drugs to modern medicines following the scientific standards of drug development [ 207 ]. Provided the potent pharmacological effects against infection, inflammation and immunity in experimental models and in clinical studies, the potential role of Echinacea may be possible and thus speculated to be beneficial.…”
Section: Limitations On the Use Of Echinaceamentioning
confidence: 99%
“…The SARS-CoV occurred in 2003, since then many natural products have shown potential in experimental studies to be developed as a candidate drug until recent years, but still there is very less focus on drug development from natural products due to numerous reasons ranging from lack of pharmacokinetic and drug formulation studies [ 204 , 205 , 206 ]. Recently, it has been suggested that a meticulous, focused and integrated approach may have the potential to develop the drugs from traditional drugs to modern medicines following the scientific standards of drug development [ 207 ]. Provided the potent pharmacological effects against infection, inflammation and immunity in experimental models and in clinical studies, the potential role of Echinacea may be possible and thus speculated to be beneficial.…”
Section: Limitations On the Use Of Echinaceamentioning
confidence: 99%
“…Among the numerous epidemics of infectious diseases that the world is facing, viral infections are undoubtedly the biggest pandemic threat in the recent era [ 1 ]. The epidemic outbreaks caused by viruses represents a critical threat to public health, particularly when preventive vaccines and effective antiviral therapies are not available [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous epidemics of infectious diseases that the world is facing, viral infections are undoubtedly the biggest pandemic threat in the recent era [ 1 ]. The epidemic outbreaks caused by viruses represents a critical threat to public health, particularly when preventive vaccines and effective antiviral therapies are not available [ 1 , 2 ]. Since December 2019, humankind has been confronted with a new coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus (SARS-CoV-2), which has infected more than 110 million people worldwide [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacognosy has a part to play in building and broadening the potential agents in this domain. 40,41 Pharmacognosy adds to, and in many places extends the ability to fight this evolving threat to human well-being and prosperity. With the wider world currently utilizing plant based medicine for treating disease, 42,43 phytobotanicals offer a unique scope within the global healthcare response as well as the research domain.…”
Section: Pharmacognosy and The Pandemicmentioning
confidence: 99%